Kontroversi Ikhtilaful Matan Hadis Menurut Ibnu Qutaibah Dalam Kitabnya Ta’wil Mukhtalif Hadis - Suganda, Bagus (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2021)
This article discusses ikhtilaful matn of hadith and its resolution methods based on the contributions of Ibn Qutaibah. Ikhtilaful matn of hadith refers to differences or contradictions in the wording of hadith. The purpose of this research is to understand how ikhtilaful matn of hadith arises and why it is prevalent today, as well as to examine the resolution methods. This study employs a qualitative approach with literature review as the research method. The main theme discussed is the controversy of ikhtilaful matn of hadith according to Ibn Qutaibah in his book